Air pollutants, economic growth and public health: implications for sustainable development in OECD countries - Mujtaba, Ghulam (Environ Sci Pollut Res Int, 2020)
The rapid economic growth over recent years and the resulting environmental pollution in OECD countries are a serious concern for the health of the general public. A comprehensive analysis of environmental pollutants, economic growth, and public health is done using data from 28 OECD economies from 2002 to 2018. Panel fully modified least squares and the panel vector error correction model are used. The results show that there is long-run causality from renewable energy and carbon dioxide (CO(2)) emissions to healthcare spending. Renewable energy and healthcare spending are positively and significantly related. It is concluded that investment in renewable energy leads to a reduction in air pollution, improvements in healthcare, and the promotion of economic growth.